2012
DOI: 10.1016/j.cemconres.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent behaviour of hardened cement paste under isotropic loading

Abstract: International audienceThe experimental results of isotropic compression tests performed at 20°C and 90°C on a class G hardened cement paste hydrated at 90°C (Ghabezloo et al., 2008, Cem. Conc. Res. 38, 1424-1437) have been revisited considering time-dependent response. Within the frame of a viscoplastic model, the non-linear responses of the volumetric strains as observed in drained and undrained tests and of the pore pressure in undrained tests are analysed. The calibration of model parameters based on experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The residual strain of –0.00088 (0.088%) was recorded at the end of stage Ⅱ after the compressive load was removed. This residual strain indicated that the C 3 S‐FA specimen underwent plastic deformation owing to the collapse of the micropores leading to the compaction of the specimen 60 and also implied the viscous strain due to the intrinsic viscoelastic properties of the cementitious paste 61,62 . The strain during stage III was –0.00252 (0.252%), which resulted in larger deformations than those that occurred during stage I; moreover, the repeated compression loading contributed to the increase in the plastic deformation of the C 3 S‐FA specimen.…”
Section: Resultsmentioning
confidence: 96%
“…The residual strain of –0.00088 (0.088%) was recorded at the end of stage Ⅱ after the compressive load was removed. This residual strain indicated that the C 3 S‐FA specimen underwent plastic deformation owing to the collapse of the micropores leading to the compaction of the specimen 60 and also implied the viscous strain due to the intrinsic viscoelastic properties of the cementitious paste 61,62 . The strain during stage III was –0.00252 (0.252%), which resulted in larger deformations than those that occurred during stage I; moreover, the repeated compression loading contributed to the increase in the plastic deformation of the C 3 S‐FA specimen.…”
Section: Resultsmentioning
confidence: 96%
“…This value approaches those for Berea sandstone at low pore pressure to total stress ratios. Vu et al () reported a cement paste (similar in poroelastic properties to calcarenite) as having a bulk viscosity of approximately 2.5 × 10 14 Pa s, and its decrease by a factor of 2 with an increase in temperature from 20 to 90 °C.…”
Section: Discussionmentioning
confidence: 99%
“…For sake of simplicity, it was however preferred in a first attempt to adopt a basic viscoelastic Kelvin-Voigt rheological model made up of an elastic spring with bulk modulus K connected in parallel with a viscous damper of viscosity ! , following the approaches adopted by Ghabezloo et al (2008), and Vu et al (2012) on hardened cement pastes.…”
Section: 2! Effects Of Volumetric Creep On Thermal Strainsmentioning
confidence: 99%